In the Face of the Strategic Choice: New Imperatives of World Policy - Ilya S. Rozhkov (Проблемы постсоветского пространства, 2017)
Collapse of the Soviet Union in 1991 and increase in the number of the Caspian Littoral States lead to the necessity of renewal of the legal status of the Caspian Sea. Former Soviet-Iranian agreements, which had previously determined the legal status of the basin, didn’t correspond with the needs of the time because of the lack of juridical regulations about such topical issues as: marine mineral exploration, environmental requirements to the mineral resources development, capture levels of the living marine resources, etc. Unilateral actions of some Littoral States didn’t ﬁnd support of their neighbors. That aggravated a situation in the region as well as adversely affected the negotiation process within the framework of the Special Working Group for drafting a Convention on the legal status of the Caspian Sea at the level of Deputy Foreign Ministers of the Littoral States. The article analyzes the core role of four Caspian Summits in the negotiation process of the Littoral States. The author underlines positive inﬂuence of the summits on establishment of multilateral cooperation mechanisms in the region as well as development of relations in the “Caspian Five”. The key benchmarks of the negotiation process are considered. Special attention is given to the legal documents of four Caspian Summits which outlined the principles of cooperation of the Caspian Littoral States. Positive balance of the First Caspian Summit (Ashgabat, 2002) is considered. The key roles of the Joint Declaration of the Second Caspian Summit (Tehran, 2007) as well as the political Statement of the Fourth Caspian Summit (Astrakhan, 2014) as political guidelines for the negotiation process on the legal status of the basin are highlighted. Great signiﬁcance of the Agreement on Security Cooperation in the Caspian Sea, which was endorsed within the framework of the Third Caspian Summit (Baku, 2010), is estimated. The author proceeds from the assumption that all efforts of ﬁve nations should be focused on forging the compromise on key issues of the draft comprehensive Convention on the Legal Status of the Caspian Sea to ﬁnalize the text of this pentalateral legal agreement as promptly as practicable and to adopt it on the Fifth Caspian Summit in Kazakhstan.